2018
DOI: 10.1111/boc.201800016
|View full text |Cite
|
Sign up to set email alerts
|

STED microscopy: A simplified method for liver sinusoidal endothelial fenestrae analysis

Abstract: This new way of analysing LSEC fenestrae will allow for expedited investigation of their dynamics, molecular composition and functions to better understand their function in liver pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…CytB heavily increased pMLC and at the same time, had no effect on fenestration diameter, other than increasing the number of fenestrations. The results are in agreement with previous reports [ 15 , 46 ]. In addition to this, we showed that CytB can be used to exacerbate the effect of other drugs on fenestrations.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…CytB heavily increased pMLC and at the same time, had no effect on fenestration diameter, other than increasing the number of fenestrations. The results are in agreement with previous reports [ 15 , 46 ]. In addition to this, we showed that CytB can be used to exacerbate the effect of other drugs on fenestrations.…”
Section: Discussionsupporting
confidence: 94%
“…Cytochalasin B (CytB) is used to depolymerise filamentous actin, and increases the number of fenestrations [ 15 ]. CytB is therefore used as a gold standard to easily induce fenestrations in LSEC (up to 300% increase in their number) within 15–60 min [ 13 , 50 ], without affecting the fenestration size [ 15 , 46 ]. We applied it to decrease the length of actin fibres.…”
Section: Methodsmentioning
confidence: 99%
“…LSEC fenestrae are important structures for liver physiology, and their loss is involved in several liver pathologies . Recently, we demonstrated that STED microscopy was suitable for LSEC fenestrae observation . Using this methodology in combination with TEM and an in vitro LSEC dedifferentiation model that mimics capillarization observed in vivo , we tested actin cytoskeleton involvement in fenestrae formation.…”
Section: Discussionmentioning
confidence: 99%
“…(12) Recently, we demonstrated that STED microscopy was suitable for LSEC fenestrae observation. (8) Using this methodology in combination with TEM and an in vitro LSEC dedifferentiation model that mimics capillarization observed in vivo, we tested actin cytoskeleton involvement in fenestrae formation. We revealed that the cytoskeleton is closely associated with fenestrae and is organized in a dense ring surrounding them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation